Persepsi Pelajar Terhadap Penggunaan Aplikasi Kahoot! dalam Pembelajaran Mobile Application di Kolej Komuniti Temerloh - Paliza binti Deraman; Norfadzilah binti Ishak (LPPM Politeknik Jambi, 2023)
There are various methods used by lecturers to measure students understanding during learning session. Besides being assessed through continuous assessment, students' understanding can also be measured through certain quizzes or games. This study was conducted to examine students' perceptions of the use of Kahoot! as online quiz media, and to investigate the effectiveness of the online formative assessment process using Kahoot!. This study was conducted to respondents consisting of 28 Sijil Teknologi Maklumat Kolej Komuniti Temerloh students who took the Mobile Application Course. A set of closed type questionnaire was used involving 2 parts, namely: Part A - demographics (2 items), and Part B - questionnaire (8 items). A quantitative research design study was used. The overall results show that the majority of students give the perception that they are interested in the use of Kahoot! in the teaching and learning process of the Mobile Application course. The results of the assessment also show that there is an improvement in student achievement. The findings of this study also suggest that the use of online quiz applications such as Kahoot! can be applied as an alternative to measure student understanding during teaching and learning sessions.